2007
DOI: 10.1007/s10951-006-0006-4
|View full text |Cite
|
Sign up to set email alerts
|

The complexity of mean flow time scheduling problems with release times

Abstract: We study the problem of preemptive scheduling n jobs with given release times on m identical parallel machines. The objective is to minimize the average flow time. We show that when all jobs have equal processing times then the problem can be solved in polynomial time using linear programming. Our algorithm can also be applied to the open-shop problem with release times and unit processing times. For the general case (when processing times are arbitrary), we show that the problem is unary NP-hard.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…Finally, let us mention that the article [23] by Lawler and Labetoulle contains explicitly, or implicitly, most (if not all) of the techniques used in this section. We nevertheless fully expose the max-stretch minimization algorithm as these techniques may not be so widely known 3 and as a good knowledge of the algorithm is necessary to understand the content of Sections 7 and 8.…”
Section: Offline Max-stretch Optimizationmentioning
confidence: 99%
“…Finally, let us mention that the article [23] by Lawler and Labetoulle contains explicitly, or implicitly, most (if not all) of the techniques used in this section. We nevertheless fully expose the max-stretch minimization algorithm as these techniques may not be so widely known 3 and as a good knowledge of the algorithm is necessary to understand the content of Sections 7 and 8.…”
Section: Offline Max-stretch Optimizationmentioning
confidence: 99%
“…Note that problem P | r j , pmtn | C j and, therefore, problem P | r j , pmtn | T j are unary NP-hard (Baptiste et al 2007). Recall that P in the notation of the problem means that all machines have identical speeds.…”
Section: Introductionmentioning
confidence: 99%
“…3.6 It is interesting to note that problem P | pmtn | U j is binary NP-hard [27], however, its complexity status under an unary encoding is still an open question. 3.7 Problem P | r j , p j = p, pmtn | C j has been solved in [1]. It is possible to prove that for problem P | r j , p j = p, pmtn | C j , an optimal schedule can be found in the class of schedules, where each job J j is processed on machine m only within an (possibly empty) interval [S j,m , C j,m [, such that C j,m ≤ S j+1,m for each m and j < n, and C j,m ≤ S j,m−1 for each m > 1 and j.…”
Section: In [28]mentioning
confidence: 99%
“…In [25], it has been shown that an optimal solution of the above linear program can be used to obtain an optimal schedule. 3.9 Problem P | r j , pmtn | C j has been proved to be unary NP-hard by a reduction from 3-partition in [1]. 3.10 Problem P | r j , p j = p, pmtn | w j C j is unary NP-hard [32].…”
Section: Minimizementioning
confidence: 99%